Subcutaneous sumatriptan for the treatment of postcraniotomy pain (SUPS trial): protocol for a randomised double-blinded placebo controlled trial - Ana Licina; Jeremy Russell; Andrew Silvers; Xin Jin; Jason Denny (BMJ Open)
Introduction Postcraniotomy pain protocols use opioids, which are considered suboptimal analgesia following this procedure. Multimodal analgesia components are sparse. Our null hypothesis states that sumatriptan is not different to placebo in addition to usual intravenous opioids, for the treatment of acute postcraniotomy pain.Methods and analysis This is a prospective single-centre randomised double-blinded placebo-controlled phase III clinical trial comparing subcutaneous sumatriptan injection in the recovery area with placebo for the treatment of postcraniotomy pain. Eligible adult patients (18 years and older) undergoing craniotomy will be identified preoperatively. Both patient groups will receive a subcutaneous injection at a point where recovery-nursing staff would initiate the usual intravenous opioid analgesia as per standardised pain management protocol. In both groups, further pain management will be followed by the usual intravenous opioid administration. Primary outcome will consist of the difference in pain experienced by the two groups of patients in recovery area 60 min after the study drug administration. Postcraniotomy pain will be measured at regular intervals using the Visual Analogue Scale (VAS) in recovery area. The minimal clinically important difference of 10 mm on the VAS between the two groups will be considered as statistically significant. We will include selected clinical and patient-reported outcomes as secondary endpoints. Univariate regression will be conducted on each one of the clinically plausible potential confounders. We will enrol a total 136 patients, with the study duration of 2 years. This trial will commence recruitment on the 1 July 2019.Ethics and dissemination This trial protocol has achieved approval by the Austin Health Research Committee, HREC/17/Austin/596. This trial was prospectively registered with Australian New Zealand Clinical Trials Registry on the 10/05/2018 with a unique trial identifier U1111-1209-9072 and registration Number ACTRN12618000793213P. Findings of this study will be disseminated in peer-reviewed academic journals.Trial registration number U1111-1209-9072, ACTRN12618000793213P